Opera as Social Status: The Private Teatro Sociale as a Reproduced Disposition to Mantua’s Cultural Habitus - Kotnik, Vlado (Italian Sociological Review, 2017)
That opera was and can still be a great source of social status, prestige, cultural and symbolic capital, is already quite well known. That it can play such a role successfully in an utterly specific and intricate manner, which today seems entirely anachronistic and obsolete, is rarer to find. One such example notorious for remaining a class in itself is connected to the Mantua opera house called Teatro Sociale, which is privately owned by the heirs of the original box-holders who built the theatre in 1822, thus in a quite different Zeitgeist than today. Since then, there have been many political and social changes for the city of Mantua, which has resulted in a noticeable transformation of just one province of a much larger foreign-domineering monarchy over the patriotic unification with other Italian lands to the democratic membership within the Republic of Italy.